Pengaruh Penyelesaian Tugas Kepala Sekolah terhadap Motivasi Kerja Guru di SMP Pahlawan Nasional Medan - Puspita Dewi; Candra Wijaya; Fatkhur Rohman (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to examine in depth the influence of completing the principal’s tasks on teacher work motivation in schools. Teacher work motivation is an important element that can influence the quality of teaching and learning in the classroom, which ultimately has an impact on student achievement. The principal has a central role in managing the school and supporting teachers through a variety of administrative and personnel tasks. Effective completion of the principal’s duties is expected to create a conducive work environment, provide clear direction, and improve the work environment. The research method used is a quantitative research method with a correlational type. This research used a total sampling technique with a sample size of all educators and education staff totaling 37. The research instrument for this research was a questionnaire consisting of 25 statements for each variable. The results of hypothesis testing show that the completion of the principal’s duties has an influence on teacher work motivation of 0.149 x 100% = 14.9%. Through the t test that has been carried out, it turns out that the t count = 4.709 while the t table value = 2.042. Because t count (4.709) > t table (2.042), this shows that there is a positive and significant contribution between the principal’s task completion variable and teacher work motivation at Pahlawan National Middle School in Medan in the form of a linear and predictive relationship via a regression line Ŷ = 126.564 + 0.855 X.